Adding pegylated interferon-α to nucleos(t)ide analogs improves HBsAg clearance in chronic hepatitis B with low-level viremia - Lilin Wang; Junfeng Lu; Dan Liu; Shan Ren; Xinyue Chen; Zhongjie Hu; Sujun Zheng (Frontiers in Medicine)
IntroductionLow-level viremia (LLV) is associated with the progression of liver fibrosis and a high risk of hepatocellular carcinoma in patients with chronic hepatitis B (CHB). The present study aimed to compare the efficacy between nucleos(t)ide analogs (NAs) therapy and combination therapy of NAs and pegylated interferon-α (pegIFN-α) in entecavir (ETV)-treated CHB patients with LLV.MethodsThis was a retrospective cohort study. ETV-treated CHB patients with LLV were included and divided into the NA group and the NA+IFN group. The NA group comprised patients switching to tenofovir alafenamide fumarate, whereas the NA+IFN group comprised those adding on pegIFN-α additionally. We compared changes in HBV markers and complete virological response (CVR) between the two groups.ResultsA total of 127 patients were enrolled, including 51 in NA+IFN group and 76 in NA group. In the NA+IFN group, the decline in HBsAg level from baseline (△ HBsAg) was significantly greater (−0.17 log10IU/mL vs. −0.06 log10IU/mL, P = 0.011) at week 24, and HBsAg clearance rate and △ HBsAg were significantly higher (8.9% vs. 0%, P = 0.017; −0.27 log10IU/mL vs. −0.11 log10IU/mL, P = 0.023) at week 48. The 48-week CVR rate in the NA+IFN group was 66.7% (34/51), which was comparable to 68.4% (52/76) in the NA group (P = 0.836).ConclusionIn ETV-treated patients with LLV, receiving NAs plus pegIFN-α tends to increase the effect of HBsAg clearance.